"Dark and dangerous designs": Tales of Oppression, Dispossession, and Repossession, 1770-1800 - Chiu, Frances (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
AbstractNot unlike the inexplicable phantasm, the Gothic novel has appeared to materialize from nowhere. Few critics have been able to explain why Gothic novelists were fixated upon the tropes of persecution, oppression, and the reclaimed birthright or why indeed they sought to resurrect a seemingly regressive, escapist folk-tale-like form despite the success of the "realistic" novels of Fielding, Richardson, and Smollett. Even fewer have been able to explain why Gothic novelists displayed so much awareness of gender issues before the publication of Mary Wollstonecraft's Vindication of the Rights of Woman in 1792. This essay begins by taking a rare glimpse into British reformist discourses of the late eighteenth century, focusing on contemporary allegations of incipient despotism and the widened appeal for universal (male) enfranchisement while also examining the new populist discursive strategies deployed by reformist writers. It demonstrates how the central themes and discursive strategies of Gothic novels from 1770 through 1800 conform to those found in contemporary reformist writing despite their lack of overt references to politics. On a larger scale, this essay shows how political discourse affects the shaping of literary genre and, conversely, how genre affects the shaping of political discourse in the rise of the so-called public sphere.